2017
DOI: 10.1088/2058-6272/aa8cbe
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on discharge process of a plasma-jet triggered gas spark switch

Abstract: The plasma-jet triggered gas switch (PJTGS) could operate at a low working coefficient with a low jitter. We observed and analyzed the discharge process of the PJTGS at the lowest working coefficient of 47% with the trigger voltage of 40 kV and the pulse energy of 2 J to evaluate the effect of the plasma jet. The temporal and spatial evolution and the optical emission spectrum of the plasma jet were captured. And the spraying delay time and outlet velocity under different gas pressures were investigated. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Inspired by the low-jitter plasma-jet triggered switch operating under a low working coefficient [19], a low jitter spark-discharge pre-ionization switch is proposed. The trigger gap configuration is adjusted to let the electrons in the spark channel of the trigger gap also become initial electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the low-jitter plasma-jet triggered switch operating under a low working coefficient [19], a low jitter spark-discharge pre-ionization switch is proposed. The trigger gap configuration is adjusted to let the electrons in the spark channel of the trigger gap also become initial electrons.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of experimental studies, a large number of studies have been carried out on the spatial and temporal evolution of the plasma jet process and the propagation mechanism. Dong et al [17] and Tie et al [18] used a highspeed camera to observe the plasma jet process, and the experiments showed that the plasma was approximately axisymmetrically distributed. The energy of the applied pulse was increased, and the transition of the plasma jet from 'bullet' to 'surge' propulsion was accelerated.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric pressure gas discharges have been used in widespread applications, including spark gap switch [1], combustion ignition [2,3], material preparation [4,5], environmental pollution control [6], and biomedicine [7]. A stable discharge is an essential basis for its applications.…”
Section: Introductionmentioning
confidence: 99%